2020
DOI: 10.3389/fnmol.2020.581018
|View full text |Cite
|
Sign up to set email alerts
|

LRR-Containing Oncofetal Trophoblast Glycoprotein 5T4 Shapes Neural Circuits in Olfactory and Visual Systems

Abstract: In mammals, the sensory experience can regulate the development of various brain structures, including the cortex, hippocampus, retina, and olfactory bulb (OB). Odor experience-evoked neural activity drives the development of dendrites on excitatory projection neurons in the OB, such as mitral and tufted cells, as well as inhibitory interneurons. OB interneurons are generated continuously in the subventricular zone and differentiate into granule cells (GCs) and periglomerular cells (PGCs). However, it remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“… 30 It was suggested that TPBG played a potential role in visual system development before and after receiving light stimulus. 30 , 60 TPBG has also been reported to selectively label inner midget RGCs in the primate retina, suggesting the importance of this protein. 61 , 62 The expression pattern of Tpbg in ACs of mouse retina has been studied previously in two high-throughput scRNA-seq studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“… 30 It was suggested that TPBG played a potential role in visual system development before and after receiving light stimulus. 30 , 60 TPBG has also been reported to selectively label inner midget RGCs in the primate retina, suggesting the importance of this protein. 61 , 62 The expression pattern of Tpbg in ACs of mouse retina has been studied previously in two high-throughput scRNA-seq studies.…”
Section: Discussionmentioning
confidence: 98%
“…We also identified a new genetic marker Tpbg , which is involved in retinal development after birth. 60 The identification of Tpbg provides a powerful genetic handle for further study of the TH2 cells. We believe our study contains sufficient novel discoveries that can contribute to the field in the study of the function of ACs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retina, TPBG may also regulate RBC dendritic branching complexity in the OPL. TPBG is a known regulator of Wnt signaling (He et al, 2015; Kagermeier-Schenk et al, 2011), which is required for functional synaptic targeting and OPL lamination in RBCs, therefore TPBG may promote RBC dendritic development through control of the Wnt pathway (Tsuboi, 2020). We didn’t detect a structural or physiological phenotype in RBC dendrites, but thorough evaluation of RBC dendritic maturation and branching using sparse labeling techniques might reveal a more subtle effect of TPBG-KO on dendritic architecture.…”
Section: Discussionmentioning
confidence: 99%
“…LPS administrations, the GL and EPL of the OB ipsilateral to the LPS-treated naris expresses significantly less vGluT1 compared to the contralateral OB or to saline-treated controls [21]. Similarly, expression of 5T4, a transmembrane glycoprotein uniquely expressed by GCs with dendrites projecting to the sEPL [74,75], is also significantly decreased throughout the sEPL of the OB ipsilateral to the LPS-treated naris after 3 weeks of administrations [21]. These data suggest that intrabulbar neural circuits may undergo synaptic pruning in response to COI in the form of decreased dendrodendritic synapses.…”
Section: Consequences Of Ob Inflammation On Different Olfactory Bulb ...mentioning
confidence: 99%